Strong molecular weight effects of gate-insulating memory polymers in low-voltage organic nonvolatile memory transistors with outstanding retention characteristics - Seo,J; Nam,S; Kim,H; Anthopoulos,TD; Bradley,DDC; Kim,Y (NPG Asia Materials, 2016)
Organic nonvolatile memory transistors, featuring low-voltage operation (less than or equal to5 V) and high retention characteristics (>10 000 cycles), are demonstrated by introducing high molecular weight poly(vinyl alcohol) (PVA) as a gate insulating layer. PVA polymers with four different molecular weights (9.5–166 kDa) are examined for organic memory devices with poly(3-hexylthiophene) channel layers. All devices show excellent p-type transistor behavior and strong hysteresis in the transfer curves, but the lower molecular weight PVA delivers the higher hole mobility and the wider memory window. This has been attributed to the higher ratio of hydroxyl group dipoles that align in the out-of-plane direction of the PVA layers, as supported by impedance spectroscopy (dielectric constants), polarized Fourier transform-infrared spectroscopy and synchrotron radiation grazing incidence X-ray diffraction measurements. However, outstanding retention characteristics (<4% current variation after 10 000 cycles) have been achieved with the higher molecular weight PVA (166 kDa) rather than the lower molecular weight PVA (9.5 kDa).